Integrating Scratch Techniques in Relief Map Media for Earth's Surface Learning - Suciani, Ayu; Islami, Zukya Rona; Nuryanti, Reni (JURNAL GEOGRAFI, 2025)
In the modern educational landscape, innovative teaching methods, such as raised-relief maps using graphic art scratch techniques, are crucial for helping students engage with complex geography concepts. These tactile maps provide a multisensory learning experience, enhancing spatial awareness and retention by allowing students to physically interact with three-dimensional topographies. By combining art and geography, this approach fosters creativity while improving students' understanding and retention of geographical features. This research uses the R&D method with the ADDIE model to design and develop a raised relief map to improve students' understanding of the Earth's topography. The development process involves creating a map prototype using scratch graphic art techniques and various materials such as plywood, foam, plaster, and acrylic paint to create three-dimensional topographic features. The results of this research indicate that raised relief maps successfully enhance students’ understanding of spatial relationships and topographic features of the Earth through an interactive, multisensory approach. The use of tactile materials and interactive elements in the maps helped students understand complex geographic concepts, while feedback from prototype testing provided insights for design improvements to enhance learning effectiveness. The contribution of this research is to provide an effective tactile-based learning aid development model to enhance students' geographical understanding, while opening up opportunities for further innovation in interactive education.